Next-Generation Manufacturing Protocols Enriching TSCM CAR T Cells Can Overcome Disease-Specific T Cell Defects in Cancer Patients - Arcangeli, Silvia; Falcone, Laura; Camisa, Barbara; De Girardi, Federica; Biondi, Marta; Giglio, Fabio; Ciceri, Fabio; Bonini, Chiara; Bondanza, Attilio; Casucci, Monica (Frontiers in Immunology, 2020)
Chimeric antigen receptor (CAR) T cell expansion and persistence emerged as key efficacy determinants in cancer patients. These features are typical of early-memory T cells, which can be enriched with specific manufacturing procedures, providing signal one and signal two in the proper steric conformation and in the presence of homeostatic cytokines. In this project, we exploited our expertise with paramagnetic beads and IL-7/IL-15 to develop an optimized protocol for CAR T cell production based on reagents, including a polymeric nanomatrix, which are compatible with automated manufacturing via the CliniMACS Prodigy. We found that both procedures generate similar CAR T cell products, highly enriched of stem cell memory T cells (TSCM) and equally effective in counteracting tumor growth in xenograft mouse models. Most importantly, the optimized protocol was able to expand CAR TSCM from B-cell acute lymphoblastic leukemia (B-ALL) patients, which in origin were highly enriched of late-memory and exhausted T cells. Notably, CAR T cells derived from B-ALL patients proved to be as efficient as healthy donor-derived CAR T cells in mediating profound and prolonged anti-tumor responses in xenograft mouse models. On the contrary, the protocol failed to expand fully functional CAR TSCM from patients with pancreatic ductal adenocarcinoma, suggesting that patient-specific factors may profoundly affect intrinsic T-cell quality. Finally, by retrospective analysis of in vivo data, we observed that the proportion of TSCM in the final CAR T cell product positively correlated with in vivo expansion, which in turn proved to be crucial for achieving long-term remissions. Collectively, our data indicate that next-generation manufacturing protocols can overcome initial T-cell defects, resulting in TSCM-enriched CAR T cell products qualitatively equivalent to the ones generated from healthy donors. However, this positive effect may be decreased in specific conditions, for which the development of further improved protocols and novel strategies might be highly beneficial.